Answer:
It looks right to me
Step-by-step explanation:
Answer:
B
Step-by-step explanation:
F(-2) = 4x(-2) = -8;
g(f(-1))= g(-8) = 2x(-8) -1 = -16 - 1 = -17.
Simply substitute x for -3 and y for -5, creating the equation shown below:
-6 (-3 - 2(-5) )
Now that you have your values set up, now you can do the math by starting off with Multiplying -2 by -5, which will get you 10.
Now that you have the parenthesis simplified in the parenthesis, you can use the distributive property by multiplying all the numbers with -6, like so:
-6(-3+10)= 18 - 60, which simplifies to -42, in which (A) is your answer.